PENGARUH WORK ENVIRONMENT (LINGKUNGAN KERJA) TERHADAP ORGANIZATIONAL COMMITMENT (KOMITMEN ORGANISASI) PEGAWAI DI LEMBAGA PEMASYARAKATAN KELAS III RANGKASBITUNG - Anggoro, Primandha; Rifani, Denny Nazaria (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Correctional Institutions are government organizations to foster prisoners who need a comfortable environment for employees so they can carry out their work optimally and optimally. Therefore, a good level of environment can influence commitment, so a work environment is needed so that employees can contribute highly to achieving organizational goals, especially in providing the best service. This research aims to determine the influence of the work environment on organizational commitment at the Rangkasbitung Class III Correctional Institution. The research method used is quantitative research with a non-experimental quantitative design by testing causal relationships (Causality-Comparative Research). The population used was all employees, totaling 63 people. The research data was obtained from the results of the questionnaire. Data analysis used univariate analysis, normality test, simple linear regression, significance test, and determination test using IBM SPSS 25 software. The research results showed that there was a positive and directly proportional influence between work environment and organizational commitment. The R square indicates that Work Environment is 45.5% influenced by existing performance and the remaining 54.5% is influenced by other variables. So, it is concluded that there is a positive influence of the work environment on organizational commitment at the Class III Rangkasbitung Correctional Institution. Keywords: Work Environment; Organizational Commitment; Correctional Institutions